Feasibility study of renewable energy using levelized cost energy - Azhar N.A.H.M.; Hock G.C.; Shaari S.A.; Yunus B.; Kiong T.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Diesel engines; Energy policy; Hydroelectric power; Hydroelectric power plants; Plant expansion; Diesel generators; Feasibility studies; Hydropower plants; Long-term sustainability; Microsoft excel; Renewable energies; Renewable energy using; Smart Micro Grids; Process control